Insights on Tropical High‐Cloud Radiative Effect From a New Conceptual Model - Jakob Deutloff; Stefan A. Buehler; Manfreth Brath; Ann Kristin Naumann (Journal of Advances in Modeling Earth Systems, 2025)
Abstract The new capabilities of global storm‐resolving models to resolve individual clouds allow for a more physical perspective on the tropical high‐cloud radiative effect and how it might change with warming. In this study, we develop a conceptual model of the high‐cloud radiative effect as a function of cloud thickness measured by ice water path. We use atmospheric profiles from a global ICON simulation with 5km horizontal grid spacing to calculate the radiation offline with the ARTS line‐by‐line radiative transfer model. The conceptual model of the high‐cloud radiative effect reveals that it is sufficient to approximate high clouds as a single layer characterized by an albedo, emissivity and temperature, which vary with ice water path. The increase of the short‐wave high‐cloud radiative effect with ice water path is solely explained by the high‐cloud albedo. The increase of the long‐wave high‐cloud radiative effect with ice water path is governed by an increase of emissivity for ice water path below 10−1kgm−2, and by a decrease of high‐cloud temperature with increasing ice water path above this threshold. The mean high‐cloud radiative effect from the ARTS simulations for the chosen day of this ICON model run is 1.25Wm−2, which is closely matched by our conceptual model with 1.26Wm−2. Because the high‐cloud radiative effect depends on the assumed radiative alternative, assumptions on low clouds make a substantial difference. The conceptual model predicts that doubling the fraction of low clouds roughly doubles the positive high‐cloud radiative effect.